Muscle contraction analysis during lifting task - Kamarudin, Nor Hafeezah; Ahmad, Siti Anom; Hassan, Mohd Khair; Mohd Yusoff, Rosnah; Md. Dawal, Siti Zawiah (IEEE (IEEE Xplore), 2014)
This study is to measure and investigate the muscle contraction during lifting tasks activities with the effect of different loads, height, angle of twisting and lifting frequency. This study involved 14 male and female participants performed the lifting tasks with different weight loads of 10kg to 24kg into the height position of 70cm and 130cm at the frequency of 1 and 6 lifts per minute with 0° and 90° of twisting angle. The Electromyogram activity was recorded from biceps and triceps muscles using the Shimmer EMG system. This method is used in determining the weight loads limit that can be lifted by the male and female participants in the manual lifting process.